2015
DOI: 10.1111/apm.12373
|View full text |Cite
|
Sign up to set email alerts
|

Association of TAP1 and TAP2 genes with susceptibility to pulmonary tuberculosis in Koreans

Abstract: Tuberculosis remains an important public health problem in Koreans. However, very few studies have reported on the genetic factors associated with TB susceptibility in Koreans. The aim of this study was to elucidate the genetic factors associated with susceptibility to pulmonary tuberculosis (PTB). We investigated the transporter associated with antigen processing -1 (TAP1) and TAP2 gene polymorphisms in 160 Korean PTB patients (categorized according to extent of lesion and TB medication history) and 210 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…Another study in Northern Columbia found a trend toward an association between TB susceptibility and the TAP2*0201 allele; however, there was no such trend after Bonferroni's correction was applied . In a Korean population, the TAP2 *0102 allele showed an association with TB, but this association was not statistically significant in our population . This discrepancy might be due to geographic variations or to differences in the genetic makeup of different populations, especially populations that are under selection pressures from different environments.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Another study in Northern Columbia found a trend toward an association between TB susceptibility and the TAP2*0201 allele; however, there was no such trend after Bonferroni's correction was applied . In a Korean population, the TAP2 *0102 allele showed an association with TB, but this association was not statistically significant in our population . This discrepancy might be due to geographic variations or to differences in the genetic makeup of different populations, especially populations that are under selection pressures from different environments.…”
Section: Discussioncontrasting
confidence: 78%
“…Association studies that examined TAP2 polymorphisms and tuberculosis susceptibility in different populations Roh et al(13) OR, odds ratio; Pc, Bonferroni's corrected p-value.…”
mentioning
confidence: 99%
“…Genetic variation in the coding region of TAP2 has been associated with tuberculosis (TB) infection in some population‐based studies (Rajalingam et al, ; Gomez et al, ; Roh et al, ; Thu et al, ). However, there are some differences in the results reported for those studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that tuberculosis susceptibility and vaccine protection are independently controlled by host genotype in a mouse model system (Smith & Proulx, ), and persons with genetic liabilities have a much higher risk to develop clinical TB disease (McShane, ). Many human immunogenetic factors, such as IFN‐gamma receptor (Lü et al., ; Park et al., ), NRAMP1 (Wu et al., ), VDR (Lee et al., ), TLR (Salie et al., ), LMP/TAP (Roh, Yoon, Shin, Song, & Park, ), IL‐10 (Liang, Guo, Li, & Kong, ) and HLA gene polymorphisms (Harfouch‐Hammoud & Daher, ; Kettaneh et al., ), have been confirmed as risk or resistance factors to tuberculosis in populations of various ethnic and geographical origins (Taype, ShaVipzzaman, Accinelli, Espinoza, & Shaw, ). However, the role of host genomic susceptibility for MDR/RR‐TB has seldom been investigated (Butov et al., ; Kim et al., ; Kuranov et al., ; Marwoto et al., ; Park et al., ; Rathored et al., ; Sharma et al., ; Singh, Balamurugan, Katoch, Sharma, & Mehra, ), which focused on human leucocyte antigens mostly.…”
Section: Introductionmentioning
confidence: 99%